Communicating sport, sustainability and social activism to generation Z: consumer perceptions - Opelík, Daniel; Voráček, Josef; Bernardová, Gabriela; Bačuvčík, Radim (Frontiers in Communication, 2025)
ObjectiveThis study aimed to identify how selected representatives of Generation Z, specifically university students, perceive Adidas marketing campaigns. The research sought to explore their perceptions, considering various aspects of the campaigns such as target audiences, media used, and messaging, in the context of Generation Z’s unique values and consumer behavior. Furthermore, the study investigated the alignment of these campaigns with the values characterizing Generation Z and the effectiveness of different communication strategies employed by Adidas.MethodsA mixed-methods approach was employed, combining quantitative and qualitative research methodologies. The quantitative phase involved an online questionnaire distributed to Generation Z students. The questionnaire assessed awareness of specific Adidas campaigns (e.g., Parley for the Oceans, Love Unites, Sportswear), emotional responses, agreement with campaign-related statements, and purchase likelihood using Likert scales and the Net Promoter Score. The qualitative phase consisted of two focus group discussions, to gain deeper insights into their perceptions and to elaborate on the quantitative findings. Thematic analysis was used to analyze the qualitative data, while descriptive statistics were conducted on the quantitative data.ResultsThe study generally indicated a moderate level of awareness regarding various Adidas marketing campaigns among the Generation Z student population. Sportspersons were more frequently recognized and perceived as more credible brand ambassadors compared to celebrities and influencers. Campaigns addressing themes of sustainability and diversity generally resonated with the respondents, suggesting an awareness and consideration of these values. However, the study also revealed a notable “paradox of Generation Z,” where despite expressing interest in sustainability and ethical considerations, price and practicality often took precedence in stated purchase intentions. Furthermore, there was a general indication of a potential disconnect between the recognition and impact of global Adidas campaigns within the specific context of the Generation Z demographic. Direct communication attempts via mobile applications were largely unnoticed and not preferred. Collaborations with youth sports leagues and the brand’s venture into NFTs also showed low levels of awareness among the respondents.ConclusionThe study concludes that while Adidas makes efforts to engage with the values of Generation Z in its marketing campaigns, the overall impact and resonance within the student demographic are nuanced. The findings highlight the importance of focusing on authentic and credible brand ambassadors, particularly from the sports domain. Despite a stated affinity for values such as sustainability and diversity, the economic realities often influence purchase decisions, underscoring the “paradox of Generation Z.” Global brands like Adidas need to carefully consider local market penetration and tailor their communication strategies to enhance recognition and impact among the Generation Z audience.